Are Evolution and the Intracellular Innate Immune System Key Determinants in HIV Transmission? - Sumner, Rebecca P.; Thorne, Lucy G.; Fink, Doug L.; Khan, Hataf; Milne, Richard S.; Towers, Greg J. (Frontiers in Immunology, 2017)
HIV-1 is the single most important sexually transmitted disease in humans from a global health perspective. Among human lentiviruses, HIV-1 M group has uniquely achieved pandemic levels of human-to-human transmission. The requirement to transmit between hosts likely provides the strongest selective forces on a virus, as without transmission, there can be no new infections within a host population. Our perspective is that evolution of all of the virus–host interactions, which are inherited and perpetuated from host-to-host, must be consistent with transmission. For example, CXCR4 use, which often evolves late in infection, does not favor transmission and is therefore lost when a virus transmits to a new host. Thus, transmission inevitably influences all aspects of virus biology, including interactions with the innate immune system, and dictates the biological niche in which the virus exists in the host. A viable viral niche typically does not select features that disfavor transmission. The innate immune response represents a significant selective pressure during the transmission process. In fact, all viruses must antagonize and/or evade the mechanisms of the host innate and adaptive immune systems that they encounter. We believe that viewing host–virus interactions from a transmission perspective helps us understand the mechanistic details of antiviral immunity and viral escape. This is particularly true for the innate immune system, which typically acts from the very earliest stages of the host–virus interaction, and must be bypassed to achieve successful infection. With this in mind, here we review the innate sensing of HIV, the consequent downstream signaling cascades and the viral restriction that results. The centrality of these mechanisms to host defense is illustrated by the array of countermeasures that HIV deploys to escape them, despite the coding constraint of a 10 kb genome. We consider evasion strategies in detail, in particular the role of the HIV capsid and the viral accessory proteins highlighting important unanswered questions and discussing future perspectives.